2019
DOI: 10.18632/aging.102372
|View full text |Cite
|
Sign up to set email alerts
|

T5224, RSPO2 and AZD5363 are novel drugs against functional pituitary adenoma

Abstract: We tested whether the drugs T5224, RSPO2, and AZD5363 exert therapeutic effects against functioning pituitary adenoma (FPA). We analysed the gene expression profiles of four FPA mRNA microarray datasets (GSE2175, GSE26966, GSE36314, and GSE37153) from the Gene Expression Omnibus database and identified genes differentially expressed in FPA vs control tissues. We then carried out Gene Ontology, Kyoto Encyclopedia of Genes and Genomes (KEGG), and protein-protein interaction network analyses. We also measured the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…T-5224 represents the small molecule inhibitor of AP-1 which has gone the furthest in clinical trials having made it to a discontinued phase II trial for its effectiveness in arthritis. It has also been shown to have anticancer activity in various models [139,140]. Further clinical study of this molecule (or the peptide from which it is derived) as an anticancer agent may prove fruitful in the future.…”
Section: Antagonising the Cjun Dbdmentioning
confidence: 99%
“…T-5224 represents the small molecule inhibitor of AP-1 which has gone the furthest in clinical trials having made it to a discontinued phase II trial for its effectiveness in arthritis. It has also been shown to have anticancer activity in various models [139,140]. Further clinical study of this molecule (or the peptide from which it is derived) as an anticancer agent may prove fruitful in the future.…”
Section: Antagonising the Cjun Dbdmentioning
confidence: 99%
“…Our results suggested that the abnormal changes including erythrocyte differentiation, neutrophil degranulation may occur in hemoglobin complex, which agreed with the previous study that obstacle to myeloproliferative differentiation may cause aplastic anemia in the progression of PMF [ 26 ]. Some studies have also demonstrated that cell membrane ion channels, such as iron ion binding, participate in cell signal transduction, proliferation, apoptosis as well as regulation of gene expression in tumor levels [ 27 , 28 ]. Furthermore, analyses of KEGG and GSEA revealed that the mutual up-regulated DEGs were chiefly enriched in the cell cycle, JAK-STAT signaling pathway and TNF signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, JUP functions as a substrate for VE-PTP and is necessary for it to stimulate VE-cadherin function in endothelial cells. In addition, mutations in JUP and/or changes in its expression levels have been identified in various cancer types (hepatoma, lung adenocarcinoma, and breast cancer) [ 38 40 ] and upregulation of it may lead to metastasis and recurrence in patients with squamous cell carcinoma [ 41 ]. Thus, we proposed that abnormal expression of JUP might also play an important role in the metastasis and recurrence of UCS.…”
Section: Discussionmentioning
confidence: 99%